O simulacro ecológico: falácia, poder e hegemonia no discurso do desenvolvimento sustentável - Casara, Marques (2016)
This research work addresses the discourse of sustainable development and its ploys to conceal predatory practices. On a planet economically administered by the logic of waste and of structural recycling, the sustainability discourse operates mediatically within a context guided by a painless minimalist ethics, which readily accepts the celebratory and spectacularized approach to sustainability, but rejects it in everything that prescribes renunciation, thrift or threat of change in the geo-economic infrastructure. In this nonrestrictive, instrumentalized and hedonistic ethics, the discourse serves to simulate responsibilities and conceal predatory practices. "Green consciousness" is readily accepted by the individual-commodity. The logic of desire overrides the logic of need and sustainability becomes a commodity exchange. In this context, a substantial portion of publications on sustainability celebrate the advent of a new way of doing business, a new way of living, with responsibility and environmental respect. However, few attempts are made to examine the issue critically. The purpose of the research is to investigate the discourse of sustainable development and its insertion into mediatic visibility, considering three actors: (1) industrial corporations responsible for the process of environmental degradation; (2) governments, which do little to contain the predatory flow, given that they are powerless to interfere in a world for which they are unprepared, and (3) civil society organizations, which started off as pioneers in defending the cause of sustainability, but later fell behind in the contest for control of the environmental discourse. In this scenario, we propose the hypothesis that companies, governments and civil society organizations, when engaging in the sustainability discourse, use it as a tool for dissuasion and concealment of what is real. The theoretical framework of this research lies within the field of Communication, based on studies about media visibility, consumer practices, cybercultural dromocracy and existence in real time. In the environmental field, particularly insofar as Communication theories are concerned, issues are analyzed pertaining to the commodification of nature and to spectacle ecology. The theoretical framework also touches upon topics pertaining to the manipulation of affects, to alienation and to hegemony. The research methodology involved a review of the literature on studies of sustainability and their discursive practices. This was followed by studies in the field of Communication that would enable a perspective view of the problem, and lastly, a qualitative survey of communication materials produced by the key actors (companies, governments and NGOs). After these surveys, a systematization was performed of the data and their relationships with the theories that analyze the state of the world today